2020
DOI: 10.3390/jpm10020029
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic (PGx) Counseling: Exploring Participant Questions about PGx Test Results

Abstract: As pharmacogenomic (PGx) use in healthcare increases, a better understanding of patient needs will be necessary to guide PGx result delivery. The Coriell Personalized Medicine Collaborative (CPMC) is a prospective study investigating the utility of personalized medicine. Participants received online genetic risk reports for 27 potentially actionable complex diseases and 7 drug–gene pairs and could request free, telephone-based genetic counseling (GC). To explore the needs of individuals receiving PGx results, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Of these, 35 met eligibility criteria and were included in the analysis. An additional two articles were identified upon reference review of eligible articles and also included in the analysis, for a final total of 37 articles [ 1 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Figure 1 summarizes the identification and selection process for inclusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 35 met eligibility criteria and were included in the analysis. An additional two articles were identified upon reference review of eligible articles and also included in the analysis, for a final total of 37 articles [ 1 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Figure 1 summarizes the identification and selection process for inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Study methodologies included closed-ended questionnaires ( n = 12) focus groups ( n = 11), semi-structured interviews ( n = 7), open-ended questionnaires ( n = 3), or a mixed-methodological approach ( n = 3). One retrospective qualitative review of correspondence between patients and genetic counselors was also included [ 52 ]. A total of 488 data elements were extracted from the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the special issue articles, Silva et al [ 5 ] and Schmidlen et al [ 6 ], focused on PGx clinical decision support. Silva et al [ 5 ] leveraged a Clinical Semantic Network framework to apply a pharmacogenomic model to patient electronic medical record data.…”
mentioning
confidence: 99%
“…Given the increasingly complex challenges to integrating medical informatics data for clinical decision-making, this framework and others like it will be needed to support precision medication management. Schmidlen et al [ 6 ] conducted a retrospective qualitative analysis of genetic counseling requests from participants in a personalized medicine research study and demonstrated the critical role that genetic counselors play in supporting providers in their communication of PGx results to patients and supporting patients in their understanding of PGx results.…”
mentioning
confidence: 99%